(Nm(B.(Np(B. (NmUSORGSKIJ PROBLEMY TWOR^ESTWA ISSLEDOWANIEs (NmONAGRAFIQs - (N|(B. (NfRIDs ((NlENINGRAD s (NmUZYKAs, 1981)
(NtWOR^ESKAQ LI^NOSTX mODESTA pETROWI^A mUSORGSKOGO KAZALOSX BY UVE DASTATO^NO IZU^ENA(B.s
Keywords: (NMONOGRAFIQs